RESPON PERTUMBUHAN STEK CABANG BAMBU AMPEL KUNING (Bambusa vulgaris Schard.Ex Wendl.var. Striata) DENGAN PEMBERIAN ZAT PENGATUR TUMBUH NAA (Naphthalein Acetic Acid) DAN Rootone F - Tia Setiawati; Noviyanti Soleha; Mohamad Nurzaman (Jurnal Pro-Life, 2018)
Yellow ampel bamboo is one type of bamboo that has economic value. One effort that can be done for maintaining the existence of bamboo population so that its can be sustainably used through the cultivation of branch cuttings. The success growth of branch cutting can improve with using plant growth regulator (PGR), such as NAA and Rootone F. The aim of this study was to get the best kind and concentration of PGR that can promote the growth of ampel yellow bamboobranch cutting. This study used experimental methods with a completely randomized design (CRD) two factors. The first factor wasthe kind of PGR which consists of two levels: z1 = NAA and z2 = Rootone F. The second factor was the concentration of PGR which consists of six levels: k1 = 0 ppm, k2 = 100 ppm, 200 ppm = k3, k4 = 300 ppm, 400 ppm = k5, and k6 = 500 ppm. Data were analyzed using ANOVA (Î± = 5%) and to know the difference between treatments used Tukey test (Î±= 5%). The results showed that the Rootone F had a better effect than NAA on the growth of yellow bamboo branch cutting. Concentration of 200 ppm was the best concentration to the growth for branch cuttings of yellow ampel bamboo. Interaction Rootone F and concentration 200 ppm showed the best result to the growth for branch cuttings ampel bamboo.Keywords :branch cutting, ampel yellow bamboo, NAA, Rootone F